Identification of bacteria using volatile organic compounds - Karami, N.; Karimi, A.; Aliahmadi, A.; Mirzajan, F.; Rezadoost, H.; Ghassempour, A.; Fallah, F. (Cellular and Molecular Biology, 2017)
The rapid diagnosis of respiratory infections has always been an important goal for medical professionals, because rapid and accurate diagnosis leads to proper and timely treatment, and consequently, reduces the costs of incorrect and long-term treatments, and antibiotic resistance. The present study was conducted with the aim of detecting volatile organic compounds (VOCs) in three bacteria: Pseudomonas aeruginosa, Acinetobacter baumannii, Klebsiella pneumoniae. Headspace of the studied bacteria, after separately culturing in two types of liquid medium in three different time-periods, was extracted by solid phase microextraction and analysed by gas chromatography mass spectrometry The analysis results of the VOCs produced by the studied bacteria indicate that some VOCs are common and some are unique in each bacterium. 1-penten-3-ol, levomenthol, and 2-octyl-1-ol for P. aeruginosa, cyclohexene, 4-ethenyl, and cis-Dihydro-Î±-terpinyl acetate for A. baumannii and 1,3-butadiene, butyraldehyde, longifolene, octyl acetate, tridecanol, dodecenal, (E)-2-hexyl ester, butanoic acid, and 5,5-dodecadinyl-1 12-diol for K. pneumoniae were identified as unique VOCs for each bacterium. Finally, it can be said that an accurate and rapid bacterial detection method can be achieved by using a tool that can detect bacterial VOCs. However, more studies are needed to design a tool for which all aspects have been assessed, so that it can give us a more complete pattern for the use of these compounds as biomarkers.